Konstruksi Budaya Suku Toraja “Rambu Solo” di Tengah Masyarakat Suku Tolaki Mekongga di Kecamatan Pomalaa Kab. Kolaka - Marsia Sumule Genggong; Hj. Erni Qomariah (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2013)
ABSTRACT Applying culture in the form of behavior or habits of each tribe is different, so it will give an identity to each appropriate tribe cultural habits. At the Toraja people are very attached to their culture in terms of death or corpse burial ceremonies, which famous as rambu solo. However, based on the results of this study revealed that the implementation of rambu solo custom procession in Pomalaa sub district of Kolaka had differences with the implementation of the customs from the native region of Tana Toraja in South Sulawesi. It was because of the neighborhoods and the culture of local communities that different with the culture of Tator ethnic. As the result of that, people there tended to simplify the traditional procession. Cultural constructions in shoreline become different from origin culture. Key words: construction, culture, rambu solo